Memberdayakan Guru Sekolah Dasar menulis karya tulis ilmiah di Kabupaten Bone - Abd. Hafid; Rosmalah Rosmalah (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The Elementary Teacher is providing services tostudents to develop students' knowledge, attitudes, and skills.Besides those three aspects, teachers are also required toimprove their career by increasing their academic promotionstarting from the level of Lector or First Class JuniorSuperintendent (III/b). There are requirements that must befulfilled in order to go to the next level of promotion forteachers. One of them is able to show physical evidence in theform of Scientific Paper (KTI). The KTI type must be a resultof Classroom Action Research (PTK) and articles. Accordingto the Head of UPTD Dua Boccoe, one of the factorsinhibiting the increased of teachers’ level is the KTIrequirement. Therefore, it was necessary to conduct a KTItraining by collaborating with PGSD Lecturers at VI Campusof UNM Bone in the form of PKM by using the workshopmethod. The objectives of this activity were (1) to provideknowledge for Dua Boccoe Elementary School teachers towrite research articles and (2) Provide writing skills, includingarticles and non-research articles for teachers of UPTDElementary School, Dua Boccoe Regency. The method usedwas a workshop strategy with lecture, question and answertechniques which aimed at providing KTI mastery andassignment methods for writing a draft and KTI development.The results of the KTI workshop activities showed that 20participants in PKM had mastered KTI knowledge and wereable to make KTI in the form of research articles in the ‘good'category.